THE COMMUNICATION SYSTEM DEVELOPMENT OF BIO AGRICULTURE LEARNING CENTER BY COMMUNITY PARTICIPATION - พงศ์กิตติวิบูลย์, สุชาดา; ปุรินทรวรกุล, ปาจารีย์ (Academic Journal Phranakhon Rajabhat University, 2018)
The research aimed to; (1) encourage and develop agriculturists in the community to become local communicators; (2) develop media and activities as well as develop the learning center as a communication space; (3) construct and communicate different messages to Bio agriculture and the learning center through participatory action research with research activities and lesson learned to visualize. The study revealed that (a) the strategies used to develop the agriculturists’ communication skills included study tours, reflection strategy, decentralization strategy, and multi-level competency strategy. (b) The development of media and activities was conducted by increasing written communication, focusing on demonstration, and designing and producing media in line with intertextuality concept. (c) The creation of new agriculturists was conducted by selecting ones from the community. The juveniles or the new generation of these agriculturists were viewed as personal media. (d) The construction and communication of different messages to the learning center was conducted by unifying all these different messages at the learning center and selecting the messages that fit the target groups. Also, the Bio agriculture learning center was constructed and interpreted as a public space or social-spatial space because the center’s direct role was to pass on knowledge, while the indirect role was to transfer experiences, emotions, and feelings. Moreover, it acted as a space to express identity and perspective of Bio agriculture. At the same time, it declared the community’s identity and power.